Private investments in modern food storage: An economic feasibility analysis for private investments in modern food storage and potential public sector roles in promoting such investments - Chowdhury, Reajul Alam; Alam, Md. Monjurul; Ali, Md. Rostom; Awal, Abdul; Hossain, Shahadat; Kalita, Prasanta Kumar; Saha, Chayan Kumer; Winter-Nelson, Alex (International Food Policy Research Institute, 2024)
Unprecedented growth in rice production in Bangladesh over the last four decades has outpaced the capacity of post-harvest operations, resulting in substantial grain losses. While production technology has changed dramatically over time, there has been relatively little private investment in transforming storage capacity in the country. This paper explores the lack of widespread private investment in improved grain storage and examines the potential for public support to stimulate greater private sector investment in modern storage. We calculate the returns to investment in bulk grain silos and hermetic cocoons that could upgrade warehouse storage, and calculate the grain loss that conversion to those technologies would prevent. We then assess the public support that would be required to trigger private investment in modern storage systems. Our analysis shows that storage in jute bags in warehouses or homes outperforms the modern technologies in terms of financial returns at observed prices. Our analysis further shows that given the observed price changes during the harvest and post-harvest periods from 2008 to 2018, cocoon and silo storage as well as conventional warehouse storage were unprofitable in most years and on average overall. Although seasonal variation in market prices for paddy is sometimes pronounced, the pattern of the variation is not sufficiently large or consistent to make paddy storage reliably profitable. Conventional warehouse storage implied an average loss of BDT 2,877/MT/season over the 20 seasons considered. Use of modern storage methods would have implied average losses of BDT 3,200/MT/season to BDT 4,950/MT/season, depending on technology used. These results imply that a public sector co-investment on the order of BDT 300/MT would be required to trigger a shift from conventional to modern storage by traders or millers. This shift would imply a reduction in grain loss of 30kg to 80kg per MT stored for a public cost of BDT 3.75 to BDT 10.00 per kilogram of loss avoided. To make it profitable for intermediaries to provide commercial storage services to farmers who currently store on-farm would require a much larger co-investment of about BDT 3,200/MT stored, implying BDT 40 to BDT 106 per kilogram of loss avoided. Removal of import tariffs on storage technologies or realization of a price premium for silo-stored or hermetically stored grain could be sufficient to encourage millers to adopt modern storage, but would be inadequate to trigger increased off-farm storage as an independent activity. There is anecdotal evidence of a price premium for paddy that has been stored using improved technology. Existence of such a premium could significantly reduce public support needed to trigger private investment in improved storage.